Research Collaboration Patterns and Knowledge Structure in Asian Islamic Educational Psychology A Bibliometric Assessment - Syafii, Hisyam; Rahmatullah, Azam Syukur; Husain Azhari; Alaldaya, Rudyn (DIMAR: Jurnal Pendidikan Islam, 2025)
This study offers a bibliometric evaluation of the development trends, collaborative networks, and knowledge framework in Asian Islamic Educational Psychology from 2010 to 2024. Data were obtained from the Scopus and Web of Science databases, resulting in 1,247 papers that satisfied the inclusion criteria. Analytical instruments including VOSviewer and Bibliometrix R were utilized to delineate co-authorship networks, co-citation trends, keyword co-occurrence, and theme progression. The findings indicate Indonesia's pivotal position as the hub of research, bolstered by its numerous Islamic higher education institutions and international partnerships with Malaysia, Brunei, Pakistan, Turkey, Saudi Arabia, and Western nations such the United States and the United Kingdom. Thematic mapping reveals three primary orientations: (1) development of conceptual and theoretical models, (2) psychological techniques in socio-religious contexts, and (3) developing current challenges such as gender, artificial intelligence, leadership, and multiculturalism. The historical progression indicates a transition from conventional themes, including higher education and pedagogy (2018–2020), to multidisciplinary subjects such as psychology, gender, and knowledge (2020–2022), culminating in a focus on balanced leadership, systematic reviews, and evidence-based methodologies (2022–2024). This study confirms that Islamic teaching Psychology in Asia is progressing beyond mere identity reinforcement to actively participating in global scientific discourse, merging traditional Islamic epistemology with contemporary psychological frameworks and technology-enhanced teaching methodologies.